Strategi manajemen peserta didik dan layanan khusus di Madrasah QITA - amatullah, shafiyah (Maliki Interdisciplinary Journal, 2025)
A combination of the words "management" and "students", management is a typical process consisting of actions in the form of planning, organizing, mobilizing, and controlling that are carried out to determine and achieve predetermined goals or objectives using human resources and other resources. In education, student management is a complex and important process. This article will provide information related to the strategy or how learner management works and some special services at Madrasah QITA. This madrasah or school is one of the new educational institutions that is still developing. Every educational institution must have special services provided. The special services provided in educational institutions aim to support and ensure students to get an optimal learning experience, create an effective learning environment and support aspects of student development both academic and non-academic.